IVUS-Guided Stent Implantation to Improve Outcome: A Promise Waiting to be Fulfilled - Rogacka, Renata; Latib, Azeem; Colombo, Antonio (Current Cardiology Reviews, 2009)
The use of intravascular ultrasound (IVUS) to improve acute angiographic results was already shown in the prestent era. Various studies demonstrated the efficacy of IVUS in balloon sizing and estimating the extent of positive remodeling. With the introduction of drug-eluting stents (DES) the rate of restenosis has been significantly reduced but a new concern, the risk of stent thrombosis, has emerged. The association of stent underexpansion with stent thrombosis was observed for bare metal stents (BMS) and DES. Until now, the criteria for IVUS optimization used in different studies have relied on distal reference or on mean reference vessel for stent or postdilatation balloon sizing. Furthermore, an important recent innovation not available in previous studies is the use of noncompliant balloons to perform high pressure post-dilatation. Universal and easily applicable IVUS criteria for optimization of stent implantation as well as randomized studies on IVUS-guided DES implantation are necessary to minimize stent malapposition and underexpansion, which in turn can positively influence the rates of stent restenosis and thrombosis.
Keywords: stent malapposition